Does crowdfunding contribute to digital financial inclusion? - Md. Abdul Halim (Research in Globalization)
This study extensively examines crowdfunding to promote and enhance digital financial inclusion. The goal of this research is to investigate the role of crowdfunding in digital financial inclusion and to establish a standardized measure for comparing the level of financial inclusion across various economies worldwide. Through a comprehensive analysis of relevant scholarly literature and empirical data, this research study presents an in-depth investigation. The study shows that crowdfunding can contribute to financial inclusion through various models, including Reward-based CrowdFunding, Community-based CrowdFunding, Segregated Client Model, Notary Model, Guaranteed Return Model, Crowd-funding Asset Securitized Model, Donation-based CrowdFunding, Equity-based CrowdFunding, and Debt-based CrowdFunding. This study also shows that Singapore maintains its top position as the most financially inclusive market. Singapore is positioned at the top regarding the pillars of government assistance, employer support, and financial system support, ranking first, second, and third, respectively. This study will provide valuable insights for organizations seeking to establish their own crowdfunding platforms, as well as individuals interested in showcasing their businesses on such platforms.